1857 R.I. Rev. Stat. 614, tit. 34, ch. 236, § 9 - (:unkn) unknown (General Publisher, 1857)
No non-commissioned officer or private shall unnecessarily, or without orders from his superior officer, come on to any place of parade with his musket, rifle or pistol loaded with balls, slugs, shot or other dangerous substance, or shall so load with same while on parade.
--
Keywords: ARMED FORCES